HUBUNGAN OBESITAS ORANG TUA TERHADAP KEJADIAN OBESITAS PADA ANAK USIA SEKOLAH DI SDN 017 KECAMATAN DUMAI TIMUR - Siti Nurjannah (STIKES HUSADA GEMILANG, 2019)
Obesity in Indonesia occurs in all age groups and in all socioeconomic level. On school children, the obesity is a serious problem because it will continue into adulthood, and is a risk factor for various metabolic and degenerative diseases. The purpose of this study is to determine the relationship between parent obesity and obesity on students at SDN 017, sub-district of East Dumai. The design of this research study was an Analytic Survey with Case Control approach, the population in this study was all obesity students of SDN 017 which number were 130 students and the number of sample were 30 students. The results highlight a significant relationship between obesity of both parents and children. Statistical test results obtained p value = 0.018 is on α 5% (0.05) which means p value < 0.005%. It is recommended to parents to always pay attention to the health status of children and maintain the nutritional intake in accordance with the needs of children and balanced with exercises that make the child’s body becomes healthier.